SISTEM PENDETEKSI KESEHATAN MENTAL REMAJA MENGGUNAKAN METODE FORWARD CHAINING DAN NAIVE BAYES - Ida Ayu Gde Suwiprabayanti Putra; Ni Luh Putu Trisnawati (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
A very important first step in helping people with mental health disorders get medical care is detection. Mental health problems and drug abuse can be detected with a tool called SDQ (for adolescents aged 10 to 17 years). The twenty-five statements in the SDQ fall into five measurable behavioral categories: (1) emotional symptoms (5 statements), (2) behavioral problems (5 statements), (3) hyperactivity (5 statements), (4) friendship problems (5 statements), and (5) prosocial behavior (5 statements). By using SDQ, this research will create an expert system, a computer-based application, to detect adolescent mental health. Expert systems can be used to solve problems in ways thought by experts. This research will build a web-based expert system that uses the PHP programming language. System and accuracy testing will be carried out using black box testing and accuracy value testing to find out whether the symptoms and diagnosis results are appropriate. The research results in the form of a prototype will be available online so that teenagers can check their mental health freely.